The Effect of Game-Based Learning Strategies on Arabic Vocabulary Acquisition and Speaking Skills among Male Undergraduate Students - K M A Ahamed Zubair; Pichchai Mohideen Hamthoon (JURNAL IJ-ATL, 2026)
This study investigates the effectiveness of game-based learning strategies in improving Arabic vocabulary acquisition and speaking skills among undergraduate learners. The research aimed to examine how crossword puzzles, Quizizz-based formative assessment, and word-guessing games influence vocabulary mastery, speaking performance, and learner engagement. A Classroom Action Research design was employed involving 30 male undergraduate students aged 18–22 years, using two iterative cycles of planning, action, observation, and reflection. Data were collected through vocabulary tests, speaking assessments, Quizizz performance records, observation sheets, and questionnaires. The findings revealed significant improvement in vocabulary scores from 52.4 to 78.6 (p < 0.001) and speaking performance from 5.2 to 7.8, with engagement rising from 40% to 75%. The study contributes to language pedagogy by demonstrating the synergistic effect of integrated game-based strategies in enhancing linguistic competence and reducing speaking anxiety. It implies that structured game-based instruction can be effectively applied in Arabic language classrooms to improve learning outcomes and student motivation.